Association between intensive periodontal treatment and spontaneous intracerebral hemorrhage—a nationwide, population-based cohort study. Issue 10 (March 2019) - Huang, Jia-Lun; Chen, Wei-Kung; Lin, Cheng-Li; Lai, Ching-Yuan; Kao, Chia-Hung; Chiang, Hsien-Hsiung; Yang, Tse-Yen; Shih, Hong-Mo
Abstract : Abstract: Periodontal disease is a chronic inflammation of periodontium and has a high prevalence. Periodontal disease has been discovered to be a possible risk factor for cerebrovascular diseases. The available evidence are not enough to set up a causal relationship between periodontal disease and cerebrovascular diseases. Patients with spontaneous intracerebral hemorrhage have high mortality rates. The present study investigated whether intensive periodontal treatment is a protective factor of spontaneous intracerebral hemorrhage and can reduce the risk of spontaneous intracerebral hemorrhage. In total, 64, 960 patients with a history of periodontal disease were picked out from the National Health Insurance Research Databases as a case-cohort from January 01, 2000 to December 31, 2010. They were divided on the basis of whether periodontal disease patients received intensive surgical treatment (treatment cohort) or not (control cohort). The periodontal disease patients in treatment and control cohorts were selected by propensity score matching at a ratio of 1:1. Incidences of spontaneous intracerebral hemorrhage in both cohorts were analyzed and compared. The total hazard of spontaneous intracerebral hemorrhage was significantly decreased in the treatment cohorts compared with the control cohorts (adjusted hazard ratio = 0.60, 95% confidence interval = 0.45–0.79). Compared with the control cohort, intensive periodontal treatment may reduce the overall incidence of spontaneous intracerebral hemorrhage, particularly in elderly patients, males, and those who received more than 2 intensive treatments.